Interpretação constitucionalmente adequada do ônus probatório no processo penal à luz da presunção de inocência - Francisco Nogueira Machado (2016)
The essay at hand was germinated during the master's program at the Federal University of Minas Gerais, under the guidance of Professor Felipe Martins Pinto. The specific research object is the burden of proof in criminal procedure and its interpretation in the light of the presumption of innocence. Starting from the hypothesis that, nowadays, the traditional theory about the burden of proof demands a constitutional hermeneutics approach, it was submitted to epistemological critique in order to confront it with a new criminal procedure paradigm designed in the 1988 Constitution with the introduction of the presumption of innocence set out in Article 5, LVII. Throughout the text were addressed points, direct and indirectly related to the research objects, such as the relationships between procedure and the Constitution and human rights treaties within the boundaries of the democratic state of law; overcoming the adversarial x inquisitorial model; the history of the presumption of innocence under the approach of the burden of proof; the traditional theory about Article 156 of the Criminal Procedure Code both in doctrine and jurisprudence. Finally, the purpose was to present a possible constitutionally proper reading of Article 156 of the CPP in light of the presumption of innocence.